THE ROLE OF SURAT UKAT IN KARO SINGALOR LAU KARO DISTRICT - Sembiring, Sugihana; Ginting, Rosita (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2019)
Changing Karo language into a modern written language is certainly not an easy matter. Karo society does not want to be involved to improve, develop, and preserve the Karo language. Therefore, in this research we will examine the role of surat ukat in Karo Singalor Lau Karo District. Surat ukat can serve as a way of life in every action in Karonese life so that people can live harmonious and peacefully. The method that used in this research is descriptive method and interview. The theory that used is cultural theory.  This study describes about the role of surat ukat in the Karo community Singalor Lau  Karo District can be distinguished on: surat ukat in deeds, surat ukat in thoughts, surat ukat in the household and surat ukat for students.  From the results above, can be concluded that the Karo people have surat ukat as a guide to life in sangkep geluh in ancient times, while in the present, the younger generation is rarely know and use the surat ukat. We suggest the Karo community to life their daily life based on surat ukat so that they can live in harmony and good.